HUMOUR AND CULTURAL REFERENCES IN COMEDY FILM SUBTITLES: INDONESIAN-ENGLISH TRANSLATION - Arbain Arbain; Dzul Rachman; Fahmi Gunawan; Saltanat A. Meiramova; Muhammad Yunus Anis; Handoko Handoko (Universitas PGRI Sumatera Barat, 2026)
Indonesian comedy films display humour not only as entertainment, but also as a potential for cultural identity that is difficult to capture in English subtitles, which must favour readability over cultural principles. While many studies have been conducted on humour translation in both Western and Asian contexts, Indonesian audio-visual translations are among the under-researched topics of this field of study that still require attention. This article aims to address this gap by analysing modes of humour, translation strategies and cultural references in two Indonesian comedy films entitled Kang Mak (a remake based on Pee Mak) and Modal Nekad that can be found on Netflix. The present study adopts a qualitative approach and adopts the framework of Long and Graesser (1988) humour taxonomy, Molina & Albir (2002, 2012) translation techniques and Davies strategies for cultural references (2003). It all resulted from the plethora of funny lines in Indonesian subtitles and English translations, which were later cross-checked with a focus group comprising linguists and translation experts. The findings show that the major types in both films are nonsense and offensive humour, while modulation, literal translation and adaptation are the main strategies used. This meant they negotiated the references, cultural or otherwise, that intersected with their founding and globalness, which reflected a balance between local distinctiveness and global oversight. Humour subtitling is presented as a form of cultural mediation, with pedagogical and professional implications for audiovisual translation that highlight the need for culturally-sensitive approaches in the practice of subtitling.